1998
DOI: 10.1161/01.cir.97.1.41
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of Benefit of Negative Inotropes in Obstructive Hypertrophic Cardiomyopathy

Abstract: Background-Drugs with negative inotropic effect are widely used to decrease obstruction in hypertrophic cardiomyopathy (HCM). However, the mechanism of therapeutic benefit has not been studied. Methods and Results-We used M-mode, two-dimensional, and pulsed Doppler echocardiography to study 11 patients with obstructive HCM before and after medical elimination of left ventricular outflow tract obstruction. We measured 148 digitized pulsed Doppler tracings recorded in the left ventricular cavity 2.5 cm apical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 44 publications
3
71
1
6
Order By: Relevance
“…The effects were similar in patients with hypertrophic cardiomyopathy. 36 In addition to LV regional features, hypertensive patients usually develop LV cavity obliteration (Figures 4a and b). Secknus et al 37 have demonstrated that LV cavity obliteration (a consistent finding in LV hypercontractility), frequently respond to dobutamine echocardiography and this may indicate a favourable outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The effects were similar in patients with hypertrophic cardiomyopathy. 36 In addition to LV regional features, hypertensive patients usually develop LV cavity obliteration (Figures 4a and b). Secknus et al 37 have demonstrated that LV cavity obliteration (a consistent finding in LV hypercontractility), frequently respond to dobutamine echocardiography and this may indicate a favourable outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Hi g h e r -p o we r p h o t o mi c r o g r a p h o f a s e r i a l s e c t i o n s h o wn i n P a n e l a ( Ri g h t , Ma s s o n t r ic h r o me s t a i n i n g ) s h o ws t h i c k e n e d s ma l l a r t e r y ( a r r o w) wi t h p e r i v a s c u l a r f i b r o s i s ( a r r o wh e a d s ) . S c a l e b a r s : L e f t , Ri g h t , 5 0 μ (12)(13)(14)(15)(16)(17). The effects have been explained by the negative inotropic action, resulting in ventricular afterload reduction and deceleration of the LV ejection acceleration (13).…”
Section: F I G U R E 4 Do B U T a Mi N E S T R E S S E C H O C A R mentioning
confidence: 99%
“…S c a l e b a r s : L e f t , Ri g h t , 5 0 μ (12)(13)(14)(15)(16)(17). The effects have been explained by the negative inotropic action, resulting in ventricular afterload reduction and deceleration of the LV ejection acceleration (13). Hamada et al (16,17) …”
Section: F I G U R E 4 Do B U T a Mi N E S T R E S S E C H O C A R mentioning
confidence: 99%
“…Left ventricular outflow tract (LVOT) obstruction is an important complication of hypertrophic cardiomyopathy, related to symptoms, functional limitations, and prognoses of the patients [1][2][3], and various types of medical and surgical interventions are performed to reduce the pressure gradient in LVOT [4][5][6][7][8][9][10][11][12][13][14][15]. The degree of dynamic obstruction seen in patients with hypertrophic obstructive cardiomyopathy (HOCM) can vary markedly by the physiological changes in preload, contractility, and afterload [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Transthoracic continuous-wave (CW) Doppler technique has been reported to be feasible to measure the peak velocity in LVOT and to calculate the pressure gradient through the simplified Bernoulli equation [19][20][21]. This method is completely noninvasive and in recent years has become a standard method to quantify the degree of LVOT obstruction and monitor the efficacy of the treatment [8][9][10][11][12][13][14]17].…”
Section: Introductionmentioning
confidence: 99%